Prevalence of pet dog ownership in an urban colony of East Delhi and awareness regarding canine zoonotic diseases and responsible pet ownership among dog owners - Vinu Cherian; Preeti Dugg; Amir Maroof Khan (Wolters Kluwer Medknow Publications, 2020)
Background: India has lowly prioritized pet-associated zoonosis as a public health priority because data regarding the same and the susceptible population involved are sparse. Objective: To find the proportion of pet dog ownership in a settled urban colony of East Delhi and to assess awareness regarding canine zoonotic diseases and responsible pet ownership. Methods: This was a cross-sectional descriptive study of 700 participants in an urban colony of East Delhi. Results: The proportion of pet dog owners was 5.4%. Only one-third (34.2%) of the respondents were aware that pets are a source of disease. A majority of pet owners (86.8%) identified rabies as a disease caused by the bite of only stray dogs. The proportion of responsible pet owners was 39.4%. Only one-tenth of surveyed households had registered their pet with the local municipal authorities, despite such registration being a compulsory requirement by law. Conclusion: This study provides us with a better understanding of the lacunae in awareness of zoonotic diseases and its preventive measures among pet owners. All pet owners have a responsibility to ensure that their pets are healthy and free from disease.